The impact of media on the legitimacy of new market categories: The case of broadband internet - Schultz, Patrick L.; Marin, Alejandra; Boal, Kimberly B. (Journal of Business Venturing, 2014)
Building on research in institutional theory and market categories, we argue that media coverage, through the effects of cognitive and sociopolitical legitimacy, influence the creation of new market categories. Using data on the broadband access industry, we develop and test a media coverage model of market category entries, demonstrating the legitimacy effects of media-based information exchange on the emergence of new market categories. We include two post hoc analyses on mediation effects to test the relationship between population density and media coverage. These results indicate a possible mediation relationship, which we discuss in the implications of our study.